Peran Posyandu Melalui Program Pemberian Makanan Tambahan (PMT) Sebagai Upaya Menurunkan Risiko Stunting Di Desa Karas Rembang - Ahmad Yulda Wildanu; Falatansya Yoga Juana; Mu’arifuddin Mu’arifuddin; Anis Sulfi Nugraheni (Jurnal Bina Desa, 2026)
It is only right that every child in this country receives adequate nutritional needs, considering Indonesia's abundant natural resources. However, not everyone has the same opportunity, as evidenced by the still relatively high stunting rates in Indonesia, including in Desa Karas, Rembang. To address this issue, the government has implemented various strategic steps and programs, one of which is the provision of supplementary food (PMT). This study aims to understand the role of Posyandu through the PMT program in reducing the risk of stunting in Desa Karas, Rembang. The analysis was conducted using a participatory method with a focus on mentoring. The results of the study show that the role of Posyandu, particularly in Desa Karas, in reducing the risk of stunting has shown positive outcomes. Various government programs, including the PMT program, have been effectively implemented. Although PMT is not the primary factor in reducing stunting rates, it has encouraged parents to pay more attention to providing adequate nutrition for their children.